ANALISIS SEBARAN VEGETASI PASAK BUMI (Eurycoma longifolia Jack.) DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KABUPATEN KAMPAR ANALYSIS OF DISTRIBUTION OF VEGETATION - Atika Azharo; Defri Yoza; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The Forest Reserve of  Kenegerian Rumbio Kampar District is one that holds a lot of conservation of germplasm one Eurycoma longifolia Jack, information regarding the distribution pattern of the forest Eurycoma longifolia Jack in the Forest Reserve of Kenegerian Rumbio was limited. This study aims to determine the analysis of vegetation and distribution patterns of Eurycoma longifolia Jack in Panoghan zone, Naghao Koto zone, and Sialang Layang zone from Forest Reserve of Kenegerian Rumbio. This study using purposive sampling method.The observation plot is made in square plot which plot size was 20 x 20 m for tree level and 10 x 10 m for the poles. The results of this study indicate that the analysis of vegetation reaches its maximum value outcome important value index is 300%. Distribution pattern of Eurycoma longifolia Jack were clumped with Morisita Index value > 1. Eurycoma longifolia Jack clumped distribution petterns caused by Eurycoma longifolia Jack seeds grow not far from the mother tree, Eurycoma longifolia Jack tolerant shade tree canopies, and by factors of edafik.Keywords: Analysis vegetation, Eurycoma longifolia Jack, Morisita Indeks,                        Forest Reserve of Kenegerian Rumbio